Direct Modification of Extracellular Vesicles and Its Applications for Cancer Therapy: A Mini-Review - Nan, Wenbin; Zhang, Chao; Wang, Hao; Chen, Hongli; Ji, Shenglu (Frontiers in Chemistry, 2022)
Extracellular vesicles (EVs) are a class of lipid membrane-bound vesicles released by various cells and mediate cell-to-cell communication. By reason of their high physiochemical stability and biocompatibility, EVs are considered as novel drug delivery system. An increasing number of studies have indicated that EVs can be modified to enhance their loading efficiency, targeting ability and therapeutic capabilities for cancer therapy. Compared with the tedious process of gene engineering approaches, direct modification of EVs is easier, faster and versatile. This mini review will summarize the prevailing approaches for direct modification of EVs. Additionally, the potential applications of modified EVs in cancer therapy are also discussed, which will help readers gain a better understanding of the technologies and applications in this field.